2001
DOI: 10.1002/ptr.742
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal activity of Trigonella foenum‐ graecum L.

Abstract: The aqueous, methanol and chloroform extracts of Trigonella foenum-graecum caused significant (p < 0.05) mortality of Meloidogyne javanica larvae. The methanol soluble fraction eluted from pure distilled water showed the highest (>92%) nematicidal activity compared with the fractions eluted from pure methanol and different ratios of chloroform and methanol indicate that the nematicidal compound was polar in nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…It has been reported that the main components of fenugreek include fixed oil, mucilage, organic phosphorus compounds, choline, trigonelline, and a saponin, which yields diosgenin on hydrolysis (Baytop, 1999). It has been shown that the seeds of T. foenum graecum have blood glucose-reducing (Madar et al, 1988;Ali et al, 1995; Al-Habori and Raman, 1998), cholesterol-lowering (Al-Habori and Raman, 1998), antinociceptive (Javan et al, 1997), and nematicidal (Zia et al, 2001) effects. They are also used for the treatment of urinary system diseases, including prostate disorders and kidney stones, in humans (Ali-Shtayeh et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the main components of fenugreek include fixed oil, mucilage, organic phosphorus compounds, choline, trigonelline, and a saponin, which yields diosgenin on hydrolysis (Baytop, 1999). It has been shown that the seeds of T. foenum graecum have blood glucose-reducing (Madar et al, 1988;Ali et al, 1995; Al-Habori and Raman, 1998), cholesterol-lowering (Al-Habori and Raman, 1998), antinociceptive (Javan et al, 1997), and nematicidal (Zia et al, 2001) effects. They are also used for the treatment of urinary system diseases, including prostate disorders and kidney stones, in humans (Ali-Shtayeh et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of mortality of the plant parasitic nematode Meloidogyne javanica in the presence of chloroform extract of Trigonella foegun-graceum seeds, at 1000 ppm, following 24 h of exposure, was 38% (Zia et al, 2001). The nematocidal action of the terpene picrodendrin P from the Euphorbiaceae plant 76.67 ± 2.89 1.67 ± 2.89 0.00 ± 0.00 15.00±5.00* 15.00 ± 5.00* 25.00 ± 10.00* 41.67 ± 2.89** >1000 Croton antisyphiliticus 80.00 ± 0.00 3.33 ± 2.89 20.00 ± 5.00 23.33±7.64 31.67 ± 2.89* 41.67 ± 2.89** 50.00 ± 10.00* >1000 *p < 0.05, **p < 0.01.…”
Section: Resultsmentioning
confidence: 96%
“…Nematicidal eff ects of fenugreek have been reported by Zia et al (2001). They noted that larvae from the common phytopathogenic soil nematode Meloidogyne javanica, which is responsible for a number of diseases in commercial and food crops in tropical, sub-tropical and temperate countries, are eff ectively killed by fenugreek.…”
Section: Pesticidal Properties Of Fenugreekmentioning
confidence: 99%